New species and records of thiodinines from North and South America (Araneae: Salticidae: Salticinae: Thiodinini) - Bustamante, Abel A.; Ruiz, Gustavo R.s. (Zootaxa, 2020)
Five new species of thiodinines are described: Atomosphyrus wandae sp. nov. (♂, from state of Piauí, Brazil); Cyllodania marietae sp. nov. (♂♀, from Ecuador); Tartamura turbo sp. nov. (♂♀, from state of Pará, Brazil); Thiodina camilae sp. nov. (♂♀, from the Dominican Republic); and Thiodina tyrioni sp. nov. (♂♀, from Arizona, U.S.A.). New records of Thiodina firme Bustamante & Ruiz, 2017, Tartamura adfectuosa (Galiano, 1977), T. agatelin Bustamante & Ruiz, 2017 and T. huao Bustamante & Ruiz, 2017 are provided.